Evaluation for occult sepsis incorporating NIRS and emergency sonography - Ng, Natalie Yu Yi; Ang, Hannah Hui En; Tan, Jacqueline Chieh Ling; Ho, Weng Hoe; Kuan, Win Sen; Chua, Mui Teng (The American journal of emergency medicine, 2018)
Purpose - We aim to determine whether the combination of regional tissue oxygen saturation (StO2) measurement using near-infrared spectroscopy (NIRS), inferior vena cava (IVC) collapsibility and ejection fraction (EF) is able to detect occult sepsis. - Methods - We included adult patients in the emergency department with at least one of the following: fever; any one component of the quick sepsis-related organ function assessment (SOFA) score; heart rate≥100 beats per minute; or white cell count <4.0×109/L or >12.0×109/L. StO2 parameters, IVC collapsibility and EF were assessed. Primary outcome was composite of admission to intensive care unit, hypotension requiring fluid resuscitation or vasopressor use, and antibiotic escalation. - Results - We included 184 patients with mean age of 55.4years and slight male predominance (51.6%). Increase in temperature (adjusted odds ratio [aOR] 3.05; 95% confidence interval [CI] 1.16 to 8.02), higher white cell counts (aOR 1.10; 95% CI 1.03 to 1.19), increase in time taken to new StO2 baseline (aOR 1.03; 95% CI 1.01 to 1.06) and reduced EF (aOR 33.9; 95% CI 2.19 to 523.64) had higher odds of achieving the primary outcome. - Conclusion - Change in StO2 and time taken to reach new StO2 baseline, combined with EF could potentially predict sepsis among patients with infection.
Gesehen am 20.04.2020